Genetic Diversity of Cultivated and Wild Capsicum Accessions from Guam and Tinian Using MIG-seq - Michael Angelo Paragas Fernandez; Hiroshi Noda; Koji Takayama; Mari Marutani (HortScience)
The genus Capsicum is a diverse group encompassing several wild and domesticated species native to tropical and temperate regions of the Americas. In cultivation, convergent domestication for desirable traits has resulted in significant morphological and genetic overlap across species, particularly within the globally distributed and economically valuable Capsicum annuum complex, which includes species such as C. annuum, Capsicum chinense, and Capsicum frutescens. In Guam, the hot pepper known as donne’ is an economically and culturally important crop first introduced by Spanish traders in the late 17th century. Since its introduction, Capsicum has become naturalized, growing in island forests as wild type and diversified as landraces maintained by local farmers and home growers. However, research on the genetic diversity of local Capsicum specimens remains limited. In this study, we used multiplexed intersimple sequence repeat genotyping by sequencing (MIG-seq) to assess the genetic diversity of 37 Capsicum accessions, including both cultivated and wild types, collected from Guam and Tinian in the Mariana Islands. Analysis of genome-wide single-nucleotide polymorphisms generated from MIG-seq strongly supported three distinct groups among the Capsicum accessions assignable to C. frutescens (n = 20), C. annuum (n = 15), and C. chinense (n = 2). Population structure analysis within the C. frutescens and C. annuum groups clustered accessions into seven and three distinct genotypic populations, respectively. The clustering of accessions into these genotypic groups elucidated shared ancestry among variants or clones of unknown origin. Furthermore, the evidence of genetic admixture in accessions between genotypic populations suggests introgression between cultivated and wild-type hot peppers and intraspecific cross-pollination between accessions. The study presents MIG-seq as a potential method for characterizing the genetic diversity in traditional Capsicum landraces, providing new knowledge of a valuable genomic resource for agriculture.